Pengembangan Media Permainan Luker pada Materi Keberagaman Karakteristik Individu untuk Siswa Kelas III Sekolah Dasar - Anggraini, Anggita Tia; Juwantara, Ridho Agung; Harjanto, Ambyah; Wardana, Dewa Gedhe Krisna (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The problems in this research are 1) the learning process is less effective, 2) the use of media in Civics learning is less than optimal, 3) students have difficulty answering problem solving and 4) students' interest in learning is low. The aim of this research is to determine the level of feasibility, practicality and effectiveness of the Luker game media on the subject of diversity of individual characteristics. This type of research is research and development that adopts the development of ADDIE (Analysis, Design, Development, Implementation and Evaluation). The instruments used are expert validation sheets, questionnaire sheets and test sheets. The results of the research show that the use of the Luker game media has a very high level of validation, seen in the following results: 1) material expert validation obtained an average score of 4.4 (very valid) and 2) media expert validation obtained an average score of 4.5 (very valid). In the practicality test, it was obtained from 1) teacher responses obtained an average score of 4.3 (very practical) while 2) student responses obtained an average score of 4.3 (very practical). Furthermore, the effectiveness of using the Luker game media on material on diversity of individual characteristics showed very good results by achieving a completion percentage of 88%, this shows that the Luker game media was declared effective. Based on this explanation, it can be concluded that the development of the Luker game media has very high feasibility, practicality and effectiveness in Civics learning on the subject of diversity of individual characteristics for class III students at SD Negeri 2 Labuhan Ratu.